Mood Box: As a Form of Recognizing the Mental Emotions of Kedung Padaringan 2 Elementary School Students as the First Step Towards a Healthy and Comfortable School - Zahro, Ainin Zain; Fakhurrozi, Alifian Akhsan; Safitri, Anggun; Nurshoba, Aurelia Marsha; Panggabean, Destyn; Wicaksono, Kresna; Salsabila, Malinda; Evi Rizal, Nasywa Nabiilah; Amla, Nur Faridatul; Samudro, Paksi; Fadila, Rahayu Deka; Sinaga, Yanti Hosianna Tri Agus; Fakhriyyah, Zahrotul (Tarqabin Nusantara Group, 2023)
Basic education is an important aspect in a country's development. The comfort of children's learning in elementary schools (SD) has a crucial role in determining the quality of their education. Children's emotions can affect their learning comfort, and managing children's moods from an early age is very necessary. One effort to increase children's learning comfort at Kedung Elementary School, Kepanjen, Malang Regency is through the implementation of the Mood Box Work Program (Proker). This program aims to create positive learning conditions, stimulate learning motivation, and reduce the impact of stress due to changes in learning patterns. In this journal, we will describe the Mood Box Program and the results of its evaluation of children's learning comfort at Kedung Elementary School. We will explore the methods, approaches and changes produced by this program in an effort to improve the quality of learning at this school. A deeper understanding of the impact of this program can provide a better view of the importance of a positive and comfortable learning environment for children in these challenging times. Through analysis and reflection on the Mood Box Program, we hope to make a positive contribution in efforts to improve the quality of basic education at Kedung Elementary School, as well as provide insight for policy makers, educators and researchers in understanding the importance of creating a learning environment that is conducive to the development of children in future.